2010
DOI: 10.1016/j.febslet.2010.04.070
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic approach reveals non‐muscle myosin influences the overall smooth muscle cross‐bridge cycling rate

Abstract: a b s t r a c tRecent evidence suggests that non-muscle myosin IIB (NMIIB) contributes to smooth muscle contraction. This study was designed to determine the effects of NMIIB on the cross-bridge cycling rate. The cross-bridge cycling rate was investigated using sinusoidal analysis. Frequency analysis revealed two asymptotes in the Bode plot of the data; and the intersection of the asymptotes (corner frequency) was higher for the B +/À strain (8.73 ± 1.10 Hz vs 16.56 ± 1.26 Hz, P < 0.05), consistent with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…There are three classes of nonmuscle (NM) myosin ( Golomb et al, 2004 ), NMIIA, NMIIB, and NMIIC, and both NMIIA and NMIIB are expressed in smooth muscle ( Gaylinn et al, 1989 ; Morano et al, 2000 ; Lofgren et al, 2003 ; Eddinger et al, 2007 ; Yuen et al, 2009 ; Guvenc et al, 2010 ; El-Yazbi et al, 2015 ), whereas NMIIC is only expressed in neuronal tissue ( Golomb et al, 2004 ; Jana et al, 2009 ). Both NMIIA and NMIIB are able to form bipolar thick filaments ( Billington et al, 2013 ), and similar to SM, myosin RLC phosphorylation promotes filament formation ( Ikebe and Hartshorne, 1985 ; Applegate and Pardee, 1992 ).…”
Section: Regulation Of Smooth Muscle Myosinmentioning
confidence: 99%
“…There are three classes of nonmuscle (NM) myosin ( Golomb et al, 2004 ), NMIIA, NMIIB, and NMIIC, and both NMIIA and NMIIB are expressed in smooth muscle ( Gaylinn et al, 1989 ; Morano et al, 2000 ; Lofgren et al, 2003 ; Eddinger et al, 2007 ; Yuen et al, 2009 ; Guvenc et al, 2010 ; El-Yazbi et al, 2015 ), whereas NMIIC is only expressed in neuronal tissue ( Golomb et al, 2004 ; Jana et al, 2009 ). Both NMIIA and NMIIB are able to form bipolar thick filaments ( Billington et al, 2013 ), and similar to SM, myosin RLC phosphorylation promotes filament formation ( Ikebe and Hartshorne, 1985 ; Applegate and Pardee, 1992 ).…”
Section: Regulation Of Smooth Muscle Myosinmentioning
confidence: 99%
“…Non‐muscle myosin is expressed in smooth muscle tissues during fetal life and early after birth, and can generate contraction with slow kinetics . In some adult smooth muscle tissues, for example, the aorta, non‐muscle myosin is expressed and involved in active contractions . The role of non‐muscle myosins has been examined in different knock‐out models .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In some adult smooth muscle tissues, for example, the aorta, nonmuscle myosin is expressed and involved in active contractions. 9,10 The role of non-muscle myosins has been examined in different knock-out models. 5,6,10 Blebbistatin, a small moleculeinhibitor of actomyosin interaction, 11 has been shown to inhibit non-muscle myosin whereas smooth muscle myosin was poorly inhibited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murphy's original hypothesis described this tonic force maintenance as being due to the formation of latch bridges or slowly detaching crossbridges formed on dephosphorylation of attached, phosphorylated cross-bridges. Over the years, several additional mechanisms have been proposed to explain the latch state: (i) Rembold and co-workers (86) have suggested the possibility that increased actin polymerization during sustained contraction of swine carotid arterial smooth muscle may contribute to the latch state; (ii) non-muscle myosin II expressed in smooth muscle cells has been implicated in the latch state (87)(88)(89); (iii) a comparison of the kinetic properties of smooth muscle myosin II with one or both heads phosphorylated at S19 suggested that singly phosphorylated myosin could account for latch bridge formation and the corresponding reduction in the rate of ATP consumption (90). The possibility arises that LC 20 diphosphorylation could play a role in the latch state and is certainly worth investigating.…”
Section: The Future Of Lc 20 Diphosphorylationmentioning
confidence: 99%